The effect of moderate intensity physical exercise on the body fat percentage in elderly women - Santosa Budiharjo Santosa Budiharjo (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2004)
Background: Postmenopausal women tend to increase the body fat percentage. A decline in estrogen level cause decrease in lipolytic process.Objective: To know the effect of moderate intensity physical exercise on body fat percentage in elderly women.Method: Pretest and posttest control design. A total amount of thirty, healthy women, 60-70 years old, was divided into three groups. The first group was treated by exercise three times a week, the second group was treated by exercise two times a week and the third group was a control group. The exercise used was D series of fitness dance for elderly created by PERWOSI Yogyakarta which is a low impact aerobic dance with moderate intensity (70-79 % maximal heart rate), 40-54 minutes/day for eight weeks.Result: The result showed that the first group revealed a significantly decrease in body fat percentage (p< 0.05). The second group revealed decrease no statistically significant in body fat percentage (p> 0.05), however there was a significant correlation between the duration of exercise and the body fat percentage (r = -0.9042).Conclusion: The low impact aerobic dance with moderate intensity, 40-54 minutes/day, three times a week, for eight weeks decreased body fat percentage.Key words: moderate intensity low impact aerobic dance - excercise frequency - body fat percentage -elderly women